2022
DOI: 10.3390/ijms231911616
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Colorectal Cancer: Impact of Oncogenic Targets Regulated by Tumor Suppressive miR-139-3p

Abstract: We recently determined the RNA sequencing-based microRNA (miRNA) expression signature of colorectal cancer (CRC). Analysis of the signature showed that the expression of both strands of pre-miR-139 (miR-139-5p, the guide strand, and miR-139-3p, the passenger strand) was significantly reduced in CRC tissues. Transient transfection assays revealed that expression of miR-139-3p blocked cancer cell malignant transformation (e.g., cell proliferation, migration, and invasion). Notably, expression of miR-139-3p marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…A unique feature of miRNAs is that the target genes of a specific miRNA differ depending on the cell. Our previous studies confirmed that the same tumor-suppressive miRNA regulates different genes depending on the cancer type [11][12][13][14]. The aim of this study was to confirm the tumor-suppressive function of miR-139-3p and to clarify the molecular networks controlled by miR-139-3p in LUAD cells.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…A unique feature of miRNAs is that the target genes of a specific miRNA differ depending on the cell. Our previous studies confirmed that the same tumor-suppressive miRNA regulates different genes depending on the cancer type [11][12][13][14]. The aim of this study was to confirm the tumor-suppressive function of miR-139-3p and to clarify the molecular networks controlled by miR-139-3p in LUAD cells.…”
Section: Introductionmentioning
confidence: 58%
“…We have generated miRNA expression signatures for various cancer types using RNA sequencing and selected tumor-suppressive miRNA candidates based on those signatures [10,[35][36][37]. Of these candidates, we identified downregulation and tumor-suppressive functions of miR-139-3p in various cancers, including bladder cancer, renal cell carcinoma, head and neck squamous cell carcinoma, and colorectal cancer [11][12][13][14]. Here, we showed that miR-139-3p functions as a tumor-suppressive miRNA in LUAD in addition to other cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector construction and dual-luciferase reporter assays were performed as described in our previous studies [ 19 , 31 ]. The vector insertion sequences are shown in Figure S1 , and the reagents used are listed in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Klimaszewska-Wisniewska et al proved that SPDL1 upregulation in CRC cells indicates chromosomal instability and long survival [ 8 ]. Yasudome et al introduced a new concept referring to the possible interaction between microRNA139 (miR-139-3p) and keratin 80, which plays a potential tumor-suppressive role [ 9 ]. Pietras et al proved that CRC cell proliferation and vascular migration are mediated by major vault proteins, which possess barrel-like structures [ 10 ].…”
mentioning
confidence: 99%